Insulin favors acute inflammatory reaction in alloxan-diabetic tilapia during infectious aerocystitis - Prado, Ed Johnny R. [UNESP]; Belo, Marco Antonio A. [UNESP]; Moraes, Alessandra C. [UNESP]; Barbuio, Roberto [UNESP]; Foz, Elizabeth P.; Faria, Vanessa P.; Sebastião, Fernanda A. [UNESP] (FapUNIFESP (SciELO), 2018)
In vertebrates, the inflammatory reaction is responsible for modulating the initial nonspecific defense until specific immunity is acquired. In this context, numerous studies in mammals have demonstrated the participation of insulin in the inflammatory response, favoring cell proliferation and the migratory capacity of endothelial cells, vascular smooth muscle cells and monocytes, as well as mediating the expression of pro-thrombotic and pro-fibrotic factors. However, little is known about the effect of this peptidic hormone on the inflammatory reaction in teleostean fish. In order to evaluate the participation of insulin in the acute inflammatory response of Nile tilapia, Oreochromis niloticus, during aerocystitis induced by Aeromonas hydrophila, and 48 aloxane-diabetic tilapia were used, constituting two groups: Diabetics treated with insulin and diabetics without treatment. After six, 24, and 48 hours of inflammatory stimulation, tilapia were submitted to deep anesthesia for euthanasia and necropsy, and thus, obtaining exudate and harvesting of the swim bladder for analysis of the inflammatory reaction. Based on this premise, the present study demonstrated the participation of insulin in the acute inflammatory reaction of alloxan-diabetic tilapia by favors the cellular accumulation in the exudate, the proliferative effect of fibrous tissue and neovascularization in the inflamed site. Such findings reinforce the old hypothesis that insulin plays an important role in the innate immune response during acute inflammatory reaction, being an important pro-inflammatory hormone. However, Nile tilapia proved to be a promising experimental model for studies and advances in research involving diabetes mellitus.
Keywords: acute inflammatory reaction; aerocystitis; Aeromonas Hydrophila; alloxan-diabetic; cichlids; clinics; diabetes; inflammation; Insulin; Oreochromis niloticus; peptidic hormones; tilapia